Abo-Gareeb Irrigation Project - Salih, Lena Majeed Matar; Al-Dulaimi, Saadi Abed Auda (Al-Adab Journal, 2020)
This research ( Abo-Gareeb Irrigation Project and its Characteristics) aims at showing the importance, location and characteristics of Abo-Gareeb Project. It concluded that the project suffers from many problems and obstacles regarding irrigation such as incompliance of utilizer with water quotas and misusing them, incompliance with working agricultural density plans by which water discharging policy is designed and project’s equipment are provided, in addition to not providing flumes for watering units in eastern and northern sectors. Furthermore the drainages have never been maintained since receiving them from implementing company .Non- maintenance of drainages caused many damages that led to stop them and then to raise the underground water level highly.